(untitled) (Journal of the Bangladesh Agricultural University, 2013)
Fighting against global hunger in the adverse climatic condition is a major concern of the governments around the globe. The pace of population growth is overwhelmingly defeating the growth in crop production. In this context, introduction of GMO is emerging as a probable solution for sustainable crop production. However, such developments are not beyond criticism. This paper assesses and evaluates the prospects and challenges of introduction of GMO in a global perspective. Experiences of GM crop cultivation in different countries are also considered. This paper is a review of all accessible literature on GMO and sustainable crop production. This review will give a flavor of the on going debate and help take decision by the interested countries regarding GMO adoption. Furthermore, on the basis of the review this paper suggests some policy recommendations. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14921 J. Bangladesh Agril. Univ. 10(2): 291-296, 2012